HYDROGEOCHEMICAL CONDITIONS OF FORMATION OF DAWSONITE MINERALIZATION IN THE BEREZOVOYARKA AREA, KUZNETSK BASIN - Shvartsev S.L. (My University, 2004)
The results of a geochemical study of groundwater in the area of dawsonite mineralization are reported. Sodic bicarbonate groundwater with pH 7.3-9.2 and a salinity of 0.4-7.2 g/l occurs in this area. The equilibrium of this water with dawsonite, calcite, gibbsite, kaolinite, montmorillonite, quartz, albite, anorthite, and analcime was investigated. A comprehensive consideration of groundwater composition and ore-forming properties of the water-rock system led to the conclusion that dawsonite is a product of aluminosilicate rock weathering. However, this mineral is formed only under conditions of delayed water exchange providing a longterm water-rock interaction and accumulation of sufficient amounts of Na+, OH-, HCO3-, CO32-, and Al(OH) 4- Al(OH)4-.